2001
DOI: 10.1093/intimm/13.8.1021
|View full text |Cite
|
Sign up to set email alerts
|

Human CC chemokine liver-expressed chemokine/CCL16 is a functional ligand for CCR1, CCR2 and CCR5, and constitutively expressed by hepatocytes

Abstract: Liver-expressed chemokine (LEC)/CCL16 is a human CC chemokine selectively expressed in the liver. Here, we investigated its receptor usage by calcium mobilization and chemotactic assays using mouse L1.2 pre-B cell lines stably expressing a panel of 12 human chemokine receptors. At relatively high concentrations, LEC induced calcium mobilization and chemotaxis via CCR1 and CCR2. LEC also induced calcium mobilization, but marginal chemotaxis via CCR5. Consistently, LEC was found to bind to CCR1, CCR2 and CCR5 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 31 publications
9
64
0
Order By: Relevance
“…H4 has been shown to be primarily expressed by eosinophils and responsible for histamineinduced migration of eosinophils (10,11). In the present study, we have demonstrated that CCL16, which is a low-affinity ligand for CCR1, CCR2, CCR5, and CCR8 (6,8), is also a novel agonist for H4. CCL16 induced vigorous calcium mobilization and chemotaxis through H4 (Figs.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…H4 has been shown to be primarily expressed by eosinophils and responsible for histamineinduced migration of eosinophils (10,11). In the present study, we have demonstrated that CCL16, which is a low-affinity ligand for CCR1, CCR2, CCR5, and CCR8 (6,8), is also a novel agonist for H4. CCL16 induced vigorous calcium mobilization and chemotaxis through H4 (Figs.…”
Section: Discussionsupporting
confidence: 56%
“…Liver-expressed chemokine (LEC)/CCL16 (2), also known as novel CC chemokine 4 (2), human CC chemokine 4 (3), lymphocyte and monocyte chemoattractant (4), and liver-specific CC chemokine 1 (5), is selectively expressed in the liver and present in the normal plasma at high concentrations (6). CCL16 was shown to be induced in monocytes by IL-10 (3) and chemotactic for monocytes and lymphocytes (3,4).…”
Section: Liver-expressedmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain why CCR1 but not CCL5 knockdown affects the cell numbers during the process of osteogenesis, one reason might be because CCR1 signaling can be activated by several different chemokines in addition to CCL5, such as chemokine (C-C motif) ligand 4 (CCL4), chemokine (C-C motif) ligand 6 (CCL6), chemokine (C-C motif) ligand 14 (CCL14), chemokine (C-C motif) ligand 15 (CCL15), chemokine (C-C motif) ligand 16 (CCL16) and chemokine (C-C motif) ligand 23 (CCL23) (12)(13)(14)(15). There might have other chemokines in addition to CCL5 secreted by hMSCs upon osteogenic induction or present in the fetal calf serum that play a role in maintaining cell numbers during the process of osteogenesis.…”
Section: Ccl5 Receptor Ccr1 Is Critical For the Osteogenic Differentimentioning
confidence: 99%
“…In the mouse, only a pseudogene has been identified to date (27,28). CCL16 is a functional ligand for CCR1, CCR2, CCR5 (29), and CCR8 (30). Recombinant CCL16 demonstrated chemotactic activity on human monocytes and lymphocytes (27).…”
mentioning
confidence: 99%